Health impacts of a scale‐up of supervised injection services in a Canadian setting: an interrupted time series analysis. (2nd December 2021) - Kennedy, Mary Clare; Hayashi, Kanna; Milloy, M‐J; Compton, Miranda; Kerr, Thomas
Abstract: Background and Aims: In response to a dramatic rise in overdose deaths due to injection drug use, there was a rapid scale‐up of low‐threshold supervised injection services (SIS), termed 'overdose prevention sites' (OPS), in Vancouver, Canada in December 2016. We measured the potential impact of this intervention on SIS use and related health outcomes among people who inject drugs (PWID). Design: Segmented regression analyses of interrupted time series data from two community‐recruited prospective cohorts of PWID from January 2015 to November 2018 were used to measure the impact of the OPS scale‐up on changes in SIS use, public injection, syringe sharing and addiction treatment participation, controlling for pre‐existing secular trends. Setting: Vancouver, Canada. Participants: Of 745 PWID, 292 (39.7%) were women, 441 (59.6%) self‐reported white ancestry and the median age was 47 years (interquartile range = 38, 53) at baseline. Measurements: Immediate (i.e. step level) and gradual (i.e. slope) changes in the monthly proportion of participants who self‐reported past 6‐month SIS use, public injection, syringe sharing and participation in any form of addiction treatment. Findings: Post OPS expansion, the monthly prevalence of SIS use immediately increased by an estimated 6.4% [95% confidence interval (CI) = 1.7, 11.2] and subsequently further increased by an estimated 0.7% (95% CI = 0.3, 1.1) per month. The monthly prevalence of addiction treatment participation immediately increased by an estimated 4.5% (95% CI = 0.5, 8.5) following the OPS expansion, while public injection and syringe sharing were estimated to immediately decrease by 5.5% (95% CI = 0.9, 10.0) and 2.5% (95% CI = 0.5, 4.6), respectively. Findings were inconclusive as to whether or not an association was present between the intervention and subsequent gradual changes in public injection, syringe sharing and addiction treatment participation. Conclusions: Scaling‐up overdose prevention sites in Vancouver, Canada in December 2016 was associated with immediate and continued gradual increases in supervised injection service engagement and immediate increases in related health benefits.